The Calcineurin-TFEB-p62 Pathway Mediates the Activation of Cardiac Macroautophagy by Proteasomal Malfunction. Issue 4 (31st July 2020) - Pan, Bo; Li, Jie; Parajuli, Nirmal; Tian, Zongwen; Wu, Penglong; Lewno, Megan T.; Zou, Jianqiu; Wang, Wenjuan; Bedford, Lynn; Mayer, R. John; Fang, Jing; Liu, Jinbao; et al.
Abstract : Rationale: The ubiquitin-proteasome system (UPS) and the autophagic-lysosomal pathway are pivotal to proteostasis. Targeting these pathways is emerging as an attractive strategy for treating cancer. However, a significant proportion of patients who receive a proteasome inhibitor-containing regime show cardiotoxicity. Moreover, UPS and autophagic-lysosomal pathway defects are implicated in cardiac pathogenesis. Hence, a better understanding of the cross-talk between the 2 catabolic pathways will help advance cardiac pathophysiology and medicine. Objective: Systemic proteasome inhibition (PSMI) was shown to increase p62/SQSTM1 expression and induce myocardial macroautophagy. Here we investigate how proteasome malfunction activates cardiac autophagic-lysosomal pathway. Methods and Results: Myocardial macroautophagy, TFEB (transcription factor EB) expression and activity, and p62 expression were markedly increased in mice with either cardiomyocyte-restricted ablation of Psmc1 (an essential proteasome subunit gene) or pharmacological PSMI. In cultured cardiomyocytes, PSMI-induced increases in TFEB activation and p62 expression were blunted by pharmacological and genetic calcineurin inhibition and by siRNA-mediated Molcn1 silencing. PSMI induced remarkable increases in myocardial autophagic flux in wild type mice but not p62 null (p62-KO) mice. Bortezomib-induced left ventricular wall thickening and diastolic malfunction was exacerbated by p62 deficiency. In cultured cardiomyocytes from wild type mice but not p62-KO mice, PSMI induced increases in LC3-II flux and the lysosomal removal of ubiquitinated proteins. Myocardial TFEB activation by PSMI as reflected by TFEB nuclear localization and target gene expression was strikingly less in p62-KO mice compared with wild type mice. Conclusions: (1) The activation of cardiac macroautophagy by proteasomal malfunction is mediated by the Mocln1-calcineurin-TFEB-p62 pathway; (2) p62 unexpectedly exerts a feed-forward effect on TFEB activation by proteasome malfunction; and (3) targeting the Mcoln1 (mucolipin1)-calcineurin-TFEB-p62 pathway may provide new means to intervene cardiac autophagic-lysosomal pathway activation during proteasome malfunction. Abstract : Supplemental Digital Content is available in the text.